Antioxidant for treatment of diabetic complications: A meta‐analysis and systematic review. Issue 6 (20th March 2022) - Zhong, Ou; Hu, Jialin; Wang, Jinyuan; Tan, Yongpeng; Hu, Linlin; Lei, Xiaocan
Abstract: Antioxidants may provide a complementary treatment for patients with chronic diseases. Nevertheless, studies that have measured the effects of antioxidant on diabetes complications have provided conflicting results. This study aimed to elucidate the association between antioxidant and diabetic complications and to develop robust evidence for clinical decisions by systematic reviews and meta‐analysis. PubMed, Embase, The Cochrane Library, Web of Science, Scopus databases were searched to collect clinical studies related to the efficacy of antioxidants in the treatment of diabetes complications from inception to May 5, 2021. Statistical meta‐analyses were performed using the RevMan 5.4 software. Stata16 software was used to detect publication bias. The data of diabetic nephropathy (DN), diabetic nonalcoholic fatty liver disease (NAFLD), and diabetic periodontitis were collected to analyze the effect of antioxidant on diabetes and the above three complications. The meta‐analysis results showed that antioxidant treatment was associated with significantly changes in the fasting plasma glucose (FPG) (standardized mean difference [SMD]: − 0.21 [95% confidence interval [CI]: − 0.33, −0.10], p < 0.001), hemoglobin A1c (HbA1c) (MD: − 0.41 [95% CI: − 0.63, −0.18], p < 0.001), total antioxidant capacity (TAC) (SMD: 0.44 [95% CI: 0.24, 0.63], p < 0.001) and malondialdehyde (MDA) (SMD: − 0.82 [95% CI: − 1.24, −0.41], p < 0.001) than the control group. Antioxidant supplements have the potential to treat three complications of diabetes. In conclusion, the meta‐analysis results indicate that antioxidant treatment is effective clinically for diabetes mellitus and its complications.